Pelaksanaan Fungsi Pengawasan Syahbandar dalam Meningkatkan Keamanan dan Keselamatan Pelayaran Kapal Wisata di KSOP Kelas III Labuan Bajo - Sadipun, Theodorus Hendrik; Sudirman, Sudirman (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2021)
The duties and responsibilities of a harbormaster are very important in providing a ship's seaworthiness certificate, sailing permit, safety, and security as well as all shipping activities in Indonesian waters. This study aims to find out and reveal the function of the postmaster in supervising the safety and security of shipping in Labuan Bajo against the porter's duties in Law No. 17 of 2008 concerning Shipping and to find out the factors that influence the function of the harbormaster in supervising the safety and security of tourist ships in Labuan Bajo. The data collection used is one of the important factors in determining the success or failure of a study selecting data, it must be considered its suitability with the type of data, and in this study collecting data using observation, documentation, and interview methods. The results of this study can be concluded that the Office of Harbormaster and Port Authority of Labuan Bajo has carried out its duties and roles in carrying out the supervisory function of the safety and security of sailing ships entering or leaving the port of Labuan Bajo. Some tasks were not carried out due to the lack of companies engaged in shipping in Labuan Bajo so the supervisory function of the harbormaster was not carried out by Law Number 17 of 2008 concerning Shipping.